Health Promotion Awareness in Barbershops and Salons: An International Cross-Sectional Survey in Japan and Thailand - Sachiko Makabe (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. Aging societies are a worldwide concern, as people are living longer than ever before. The success of the “barbershop project” in improving community health in the USA suggests that the aging issue can be tackled using this method even in Asia. Nevertheless, the health promotion awareness of barbers/stylists has barely been reported in Asia. This study aimed to identify the health promotion awareness of barbers and stylists in Japan and Thailand. An international cross-sectional survey was conducted between March and December 2017. Questionnaire contents included the “current status of existing health-promotion-related services,” “awareness of contribution to maintaining people’s health,” and “awareness of collaboration with health care professionals.” Participants were 99 Japanese and 101 Thai shop owners. In Japan, more health-promotion-related services were already provided through shops, and health care awareness was higher than in Thailand. In both countries, some shops were willing to collaborate with health care professionals. In Japan, “barbers/stylists have consultation opportunities with health care professionals,” “health-related leaflets are provided,” “development of therapy/care,” and “barbershops/salons become a bridge between communities and hospitals” were mentioned as ideas for collaboration. In conclusion, barbers/stylists are highly interested in health due to the direct connection between beauty and health. Collaboration between barbershops/salons and health care professionals is possible, especially in Japan due to its super-aging society. Further development of the barbershop/salon project is needed.